2009
DOI: 10.2337/db09-0747
|View full text |Cite
|
Sign up to set email alerts
|

GAD Antibody Positivity Predicts Type 2 Diabetes in an Adult Population

Abstract: OBJECTIVETo evaluate the significance of GAD antibodies (GADAs) and family history for type 1 diabetes (FHT1) or type 2 diabetes (FHT2) in nondiabetic subjects.RESEARCH DESIGN AND METHODSGADAs were analyzed in 4,976 nondiabetic relatives of type 2 diabetic patients or control subjects from Finland. Altogether, 289 (5.9%) were GADA+—a total of 253 GADA+ and 2,511 GADA− subjects participated in repeated oral glucose tolerance tests during a median time of 8.1 years. The risk of progression to diabetes was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 37 publications
7
54
1
Order By: Relevance
“…several years before diabetes was diagnosed. A recent prospective study reported that GADA positivity in nondiabetic cases markedly increased the risk of future diabetes [19]. We found that those who were antibody-positive both in the prediabetic and diabetic state were phenotypically more similar to individuals with type 1 diabetes compared with those who were positive only after the diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 48%
“…several years before diabetes was diagnosed. A recent prospective study reported that GADA positivity in nondiabetic cases markedly increased the risk of future diabetes [19]. We found that those who were antibody-positive both in the prediabetic and diabetic state were phenotypically more similar to individuals with type 1 diabetes compared with those who were positive only after the diagnosis of diabetes.…”
Section: Discussionmentioning
confidence: 48%
“…It is possible that genes not associated with GADA explain the association between family history of type 1 diabetes and non-insulin-dependent diabetes. This is supported by the fact that the effect of family history of type 1 diabetes on risk of diabetes was independent of GADA and that the genetic background of type 1 diabetes and GADA differs (2,14,15). Alternatively, the association might be due to shared environmental factors.…”
Section: Discussionmentioning
confidence: 91%
“…In the Botnia Prospective Study, we followed 2764 initially nondiabetic relatives or spouses of type 2 diabetic patients (2,16,17). Information about firstto third-degree family history of type 1 and type 2 diabetes was retrieved from questionnaires or clinical investigation of the relatives.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations